BNT162b2 vaccine induces antibody release in saliva: a possible role for mucosal viral protection?. Issue 5 (19th April 2022) - Darwich, Abbass; Pozzi, Chiara; Fornasa, Giulia; Lizier, Michela; Azzolini, Elena; Spadoni, Ilaria; Carli, Francesco; Voza, Antonio; Desai, Antonio; Ferrero, Carlo; Germagnoli, Luca; ,; et al.
Abstract: Vaccination against an airborne pathogen is very effective if it induces also the development of mucosal antibodies that can protect against infection. The mRNA‐based vaccine‐encoding SARS‐CoV‐2 full‐length spike protein (BNT162b2, Pfizer/BioNTech) protects also against infection despite being administered systemically. Here, we show that upon vaccination, cognate IgG molecules are also found in the saliva and are more abundant in SARS‐CoV‐2 previously exposed subjects, paralleling the development of plasma IgG. The antibodies titer declines at 3 months from vaccination. We identified a concentration of specific IgG in the plasma above which the relevant IgG can be detected in the saliva. Regarding IgA antibodies, we found only protease‐susceptible IgA1 antibodies in plasma while they were present at very low levels in the saliva over the course of vaccination of SARS‐CoV‐2‐naïve subjects. Thus, in response to BNT162b2 vaccine, plasma IgG can permeate into mucosal sites and participate in viral protection. It is not clear why IgA1 are detected in low amount, they may be proteolytically cleaved. Synopsis: BNT162b2 vaccine is responsible for a strong antibody response in the plasma and in the saliva of vaccinated individuals. SARS‐CoV‐2‐specific IgG and IgA1 present in the plasma likely reach the saliva through the gingival microvasculature and crevicular fluid. We found that BNT162b2 induced: high levels of SARS‐CoV‐2‐specific IgG and IgA1 in the plasma of naïve vaccinated individuals 7–10 days after the second dose (T2). high levels of SARS‐CoV‐2‐specific IgG in the saliva of naïve vaccinated individuals 7–10 days after the second dose (T2). These scenarios are observed also in SARS‐CoV‐2 previously exposed subject already after the first dose (T1). Only very low levels of protease‐susceptible SARS‐COV‐2‐specific IgA1 are detected in the saliva of both vaccinated naïve and SARS‐CoV‐2 previously exposed subjects. Abstract : BNT162b2 vaccine is responsible for a strong antibody response in the plasma and in the saliva of vaccinated individuals. SARS‐CoV‐2‐specific IgG and IgA1 present in the plasma likely reach the saliva through the gingival microvasculature and crevicular fluid.